2020
DOI: 10.3389/fendo.2020.568864
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Artemether in Db/Db Mice Involves Regulation of AMPK and PI3K/Akt Pathways

Abstract: The traditional Chinese medicine has long been used in the treatment of diabetes, one major disease threatening the public health. It has been reported that artemether exerts antidiabetic effects on type 2 diabetes in db/db mice, however the underlying mechanisms remain unknown. In the present study, we show that artemether regulates expression of related enzymes participating in the glucose and lipid metabolism in the liver of db/db mice, which could at least partly explain the improved glucose and lipid meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…We found both Pi3k and Akt were suppressed in db/db mice ( Fig. 2 E), consistent with previous studies [ 46 ]. However, neither Pi3k nor Akt were activated in the PP group compared to the DM group, although Akt had an upward trend ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…We found both Pi3k and Akt were suppressed in db/db mice ( Fig. 2 E), consistent with previous studies [ 46 ]. However, neither Pi3k nor Akt were activated in the PP group compared to the DM group, although Akt had an upward trend ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…ART inhibited the production of intracellular lipids in a dose-dependent manner, decreased the levels of TG and the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ), fatty acid synthase (FAS), and perilipin A, which affected adipocyte differentiation ( Jang, 2016 ). In addition, artemether reduced TG and TC levels and the expression of FAS in db/db mice, and it increased liver lipid metabolism-related enzymes, such as PPARα, acetyl-CoA carboxylase 1, and carnitine palmitoyl transferase 1 ( Bai et al, 2020 ).…”
Section: Role Of Artemisinin and Its Derivatives In Kidney Diseasementioning
confidence: 99%
“…In addition, we have reported that the antimalaria artemisinin drugs induced transdifferentiation of pancreatic α cells into insulin‐producing cells 9 . The therapeutic effects of artemisinins on the insulin insufficiency and metabolic disorders of rodent diabetic models, as well as the underlying mechanism, have been broadly validated in multiple independent studies 10–18 …”
Section: Introductionmentioning
confidence: 96%
“… 9 The therapeutic effects of artemisinins on the insulin insufficiency and metabolic disorders of rodent diabetic models, as well as the underlying mechanism, have been broadly validated in multiple independent studies. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation